Phenotypic and genetic alterations of Burkholderia pseudomallei in patients during relapse and persistent infections - Seng, Rathanin; Phunpang, Rungnapa; Saiprom, Natnaree; Dulsuk, Adul; Chewapreecha, Claire; Thaipadungpanit, Janjira; Batty, Elizabeth M.; Chantratita, Wasun; West, T. Eoin; Chantratita, Narisara (Frontiers in Microbiology, 2023)
The bacterium, Burkholderia pseudomallei is the causative agent of melioidosis, a severe tropical disease associated with high mortality, relapse and persistent infections. Melioidosis treatment requires prolonged antibiotic therapy, but little is known about relapse and persistent infections, particularly the phenotypic and genetic alterations of B. pseudomallei within patients. Here, we performed pulsed-field gel electrophoresis (PFGE) to compare the bacterial genotype between the initial isolate and the subsequent isolate from each of 23 suspected recurrent and persistent melioidosis patients in Northeast Thailand. We used whole-genome sequencing (WGS) to investigate multilocus sequence types and genetic alterations of within-host strain pairs. We also investigated the bacterial phenotypes associated with relapse and persistent infections, including multinucleated giant cell formation (MNGC) efficiency and intracellular multiplication. We first identified 13 (1.2%) relapse, 7 (0.7%) persistent, and 3 (0.3%) reinfection patients from 1,046 survivors. Each of 20 within-host strain pairs from patients with relapse and persistent infection shared the same genotype, suggesting that the subsequent isolates arise from the infecting isolate. Logistic regression analysis of clinical data revealed regimens and duration of oral antibiotic therapies as risk factors associated with relapse and persistent infections. WGS analysis demonstrated 17 within-host genetic alteration events in 6/20 paired isolates, including a relatively large deletion and 16 single nucleotide polymorphism (SNP) mutations distributed across 12 genes. In 1 of 20 paired isolates, we observed significantly increased cell-to-cell fusion and intracellular replication in the second isolate compared with the initial isolate from a patient with persistent infection. WGS analysis suggested that a non-synonymous mutation in the tssB-5 gene, encoded an essential component of the type VI secretion system may be associated with the increased intracellular replication and MNGC formation efficiency of the second isolate of the patient. This information provides insights into genetic and phenotypic alterations in B. pseudomallei in human melioidosis, which may represent a bacterial strategy for persistent and relapse infection.